Asparaginase-Induced Hypertriglyceridemia Presenting as Pseudohyponatremia during Leukemia Treatment - Ashley Hinson; Dorothee Newbern; Corinne M. Linardic (Hindawi Limited, 2014)
Asparaginase is a chemotherapeutic agent used to induce disease remission in children with acute lymphoblastic leukemia (ALL). We describe the cases of two females with ALL who developed pseudohyponatremia as a presentation of hypertriglyceridemia following asparaginase treatment. Nine similar published cases of asparaginase-induced hypertriglyceridemia and its complications are also discussed. Possible mechanisms of action include inhibition of lipoprotein lipase, decreased hepatic synthesis of lipoprotein, and increased synthesis of VLDL. Effects of asparaginase-induced hypertriglyceridemia range from asymptomatic to transaminasemia, pancreatitis, and life-threatening thrombosis or hyperviscosity syndrome. All cases of hypertriglyceridemia described resolved following cessation of asparaginase treatment ± further treatments.